Recycling materials from degraded lithium-ion batteries for Na-ion storage. (March 2020) - Li, Yong; Ye, Daixin; Sun, Yanting; Wang, Yong; Shi, Bin; Liu, Wen; Guo, Rui; Pei, Haijuan; Zhao, Hongbing; Zhang, Jiujun; Zhang, Lei; Xie, Jingying; et al.
Abstract: In order to improve capacity decay and poor rate capability of CoS2 electrode, ingenious integration of both advanced material design and highly efficient electrode structure is crucial and desirable. Herein, we demonstrate a novel strategy to achieve this purpose by designing and synthesizing a single-walled carbon nanotube/reduced Graphene-oxides/CoS2 @graphitic carbon (SWCNT-rGO-CoS2 -C) nanocomposite membrane with high mechanical flexibility and Na-ion storage properties, in which CoS2 –C composite with core-shell structure was synthesized utilizing spent Li-ion batteries materials as precursors through a facile heat-treatment method. Benefiting from the synergistic effect of CoS2 nanoparticles embedding into the graphitic carbon and flexible membrane electrode with 3D network architecture, the SWCNT-rGO-CoS2 -C electrode with high content of active material (55.37 wt% in the whole electrode including current collector) exhibits improved cycling stability (709.9 mAh g −1 after 1000 cycles with a small capacity decay ratio of 0.00949% at 3000 mA g −1 ) and superior rate capability (discharging specific capacity of 533.3 mAh g −1 at 20000 mA g −1 ), which is proved to be ascribed to the partial pseudocapacitive behaviors during the sodiation and desodiation process. This approach is not only mitigating environment pollution and reducing waste of resources, but also achieving the energy recycling, and holds great application prospects in wearable and lightweight energy storage devices. Highlights: CoS2 -carbon was synthesized using waste separator and LiCoO2 as raw materials. A flexible SWCNT/rGo-CoS2 -C membrane electrode was further fabricated for SIBs. Advanced materials design and efficient electrode structure were both employed for CoS2 . The superior rate capability is ascribed to the partial pseudo-capacitive behaviors. Fade mechanism analysis of CoS2 electrode was proposed and discussed.